Padrões privados na Organização Mundial do Comércio: limites entre as regras multilaterais e a governança privada de temas ambientais, sanitários e fitossanitários - Lima, Rodrigo Carvalho de Abreu (2016)
The goal of this research is to analyze whether the World Trade Organization regulates the design, adoption and the effects of private standards on international trade, established with the aim at achieving environmental, sanitary and phytosanitary purposes, or if this agenda is purely private and falls outside the rules of the multilateral trading system. With the surge of different private standards, usually created by industries, banks, NGOs, producers, supermarkets, academy and including, in some cases, WTO Members, the developing countries and least developed countries raise concerns about possible trade barriers, which is becoming a common agenda for the Committee on Technical Barriers to Trade, the Committee on Sanitary and Phytosanitary Measures and the Committee on Trade and Environment. Assess whether the WTO regulates the private standards, or how it contemplates the discussions around reducing greenhouse gas emissions, biodiversity conservation and water use, becomes essential considering that the environmental agenda gains strength and entails the adoption of measures that may affect international trade. This research considers the evolution of environmental issues in the GATT-WTO system as a way to set parameters of the multilateral trading rules related to those issues. In addition, it will detail the different models of private standards and organizations that encourage standardization as a means to achieve environmental objectives or related food safety goals. Finally, the case law of the GATT-WTO will be considered, in order to assess if the WTO has jurisdiction or not over private standards. Hence, the main objective of the thesis is to question the WTO's ability to regulate the adoption of private standards and, in addition, discuss how this debate can evolve under the TBT and the SPS Agreements, or even in the Committee on Trade and Environment